The Influence of Graphene On The Mechanical Properties And Hydrothermal Aging Of 3 Mol% Yttria Stabilised Tetragonal Zirconia Polycrystalline At Various Sintering Conditions - Chong, Chee Hung (2020)
3 mol% Yttria stabilised Tetragonal Zirconia Polycrystalline or more commonly known as 3Y-TZP, is a type of engineering ceramic Zirconia (ZrO2). 3Y-TZP possesses outstanding mechanical properties. as well as great aesthetic value and biocompatibility. This results in 3Y-TZP to be highly demanding material in medical field market as prosthetic implant. However, one of the disadvantages of 3Y-TZP includes complication in mechanical properties caused by hydrothermal aging, which refers to spontaneous phase transformation of zirconia from tetragonal (t) into monoclinic (m) phase when it is exposed to humid condition at temperature around 65 ºC to 300 ºC. This condition is known as low temperature degradation (LTD). The purpose of this research is to study the effect of adding 0.2 wt% graphene additive on the mechanical properties, grain morphology and hydrothermal aging effect of 3YTZP at different sintering conditions. The samples were sintered at the range of 1200 ºC to 1400 ºC temperature, with different sintering holding time of 6 min, 1 hr and 2 hrs. The results showed that both graphene doped and undoped 3YTZP samples exhibited fully tetragonal phase before aging. After 12 hrs of hydrothermal aging under 180 ºC, graphene doped 3Y-TZP was observed to have 0 % monoclinic contents, compared to 4.71 % of undoped 3Y-TZP, at sintering conditions of 1400 ºC / 2 hrs. At sintering temperature of 1400 ºC, the relative density of the 3Y-TZP samples was generally higher, with the maximum at 97.83 % relative density. Meanwhile, graphene additive improved the relative density results of 3Y-TZP at 1200 ºC sintering temperature. In terms of Vickers hardness, graphene doped 3Y-TZP at sintering temperature and holding time of 1400 ºC and 6 min respectively achieved the value of 14.81 GPa, highest among other samples. Furthermore, addition of graphene was discovered to be effective in improving fracture toughness of 3Y-TZP at sintering temperature of 1400 ºC. SEM microstructure images revealed that addition of 0.2 wt% graphene additive did not have any effect on the grain morphology and average grain size of 3Y-TZP at sintering temperature of 1200 ºC. One critical finding revealed that graphene doped 3Y-TZP at 1400 ºC, 6 min sintering conditions showed promising result in terms of mechanical properties and resistance to hydrothermal aging.